Performance of turbo equalized double window cancellation and combining in large delay spread channels - JunHwan Lee; Ohtsuki, Tomoaki; Nakagawa, Masao (2009 IEEE 20th International Symposium on Personal, Indoor and Mobile Radio Communications, 2009)
In the orthogonal frequency division multiplexing (OFDM) the multipath exceeding a guard interval (GI) is one of obstacles for high data rate transmission. For the purpose of the interference suppression the authors have proposed the canceller algorithm naming DWCC, where the canceller operation is based on decision feedback equalization (DFE), but the performance of the canceller is still subject to the frequency selectivity since the tentative symbol detection at the deep faded subcarriers could not be reliable. In this paper turbo equalized double window cancellation and combining (TE-DWCC) is proposed. Throughout the paper, it is found that the error rate performance of TE-DWCC depends on how to incorporate the channel decoding gain from turbo equalization into DWCC. In addition, it is also shown that TE-DWCC is more compatible with the hard decision feedback (HDF) rather than the soft decision feedback (SDF) due to the ICI elimination method. Finally, by varying interference level, code rate, and decision feedback type, the performances of TE-DWCC are compared with the conventional canceller that adopts turbo equalization in the exponentially distributed slow fading channel.